Diversity and abundance of littoral cladocerans and copepods in nine Ecuadorian highland lakes - Torres, Leticia E.; Rylander, Kent (Revista de Biología Tropical, 2006)
The diversity and abundance of littoral cladocerans and copepods were studied in nine lakes at Reserva Ecológica Cayambe-Coca (Páramo de Guamaní), Ecuador. Six samples were taken in the littoral zone of each lake using a 500 μm mesh plankton conic net. One species of cladocerans (Ephemeroporus acanthoides) is reported for the first time in Ecuador. The diversity (H’) and evenness (E) of the lakes were determined and cor-related with PCA axes based on their environmental variables. The principal parameters that distinguished these lakes were altitude and pH, an unexpected finding considering that the altitudinal range was very small. Lake size is of secondary importance for this group of lakes. None of the environmental axes correlated with H’ or E; nevertheless, a larger than expected species richness was found in a small oligotrophic lake with a high level of DO. Based on our results, we hypothesize that altitude and pH are important factors determining the zooplankton diversity (directly or indirectly) in highland lakes.